Developing the Students’ Character through Literacy Activities in A Child-Friendly School Model - Farikah, Farikah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This case studyaimed at investigating the implementation of literacy activities in developing the students’ character of SD Negeri Secang 1 as one of child-friendly school models in Magelang Regency developed by Lund University, Sweden. This study described the practical guidance on literacy activities of child-friendly schools in developing the students’ character through the literacy programs. Since it was a case study, the writer only focused on one school and the result could not be used to generalize to child friendly schools in Indonesia. Interview and observation were used in collecting the data of this study. The interview was used to gain information on how literacy activities were normally conducted at SD Negeri Secang 1 as a friendly school model and observation was used to see the real implementation of Literacy activities in developing the students’ character. Based on the data analysis, it revealed that through literacy activitiesof a 15-minute reading activity, the students were able to develop their characters. By reading different topics, they could build their knowledge and values based on the topics they read.